Gambaran Hasil Pemeriksaan Kadar Trigliserida Pada Petugas Perawatan Lantai 4 Rsu Wisata Universitas Indonesia Timur Makassar 2018 - Reni Sarira; Andi Auliyah Warsyidah; Nardin Nardin (Jurnal Media Laboran, 2017)
Triglycerides are a type of fat that can be found in the blood and are also substances stored in tissues as a result of the conversion of most types of fat in the body, triglycerides are the main cause of arterial diseases which are usually compared to cholesterol by using electrophoretic lipoproteins. Immediate administration of statins may reduce plasma lipid levels so that it will produce better outcomes in acute ischemic patients. The aim of the study was to find out the results of the triglyceride level examination at the 4th floor maintenance officer of the General Hospital of Universitas Indonesia Timur Makassar in 2018. The benefits of this research were to increase knowledge and direct experience in conducting research and making scientific papers. The sample in this study was the blood of the 4th floor maintenance staff examined using mindray BS 200E. The samples taken in this study were 5 samples taken using purposive sampling technique and the method used was PAP-GPO (Glycerol Peroxidase Para Amino Phenazone). Based on the research that has been done on the description of the results of the examination of triglyceride levels on the 4th floor of UIT Makassar Hospital Hospital in 2018, triglyceride levels were obtained on the 4th floor care workers, from 5 examination samples the percentage of triglycerides was 80% abnormal and 20 as normal. %.